1974
DOI: 10.1139/e74-016
|View full text |Cite
|
Sign up to set email alerts
|

Taphonomy and Taxonomy of the Early Ordovician Gastropod Ceratopea canadensis (Billings), 1865

Abstract: Several hundred silicified specimens of Pleurotomaria canadensis Billings, 1865 and other rare fossils indicative of a late Canadian age have been collected from the Oxford Formation, southwest of Ottawa, Ontario. Redescription of this neglected gastropod species permits its assignment to the genus Ceratopea. even though no ceratopean opercula have been found.Rare faunal elements include ribeirioids and open coiled gastropods that may have lived, respectively. in and on a mud bottom. There is no evidence that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…R. calcifera is known from several localities in the Beekmantown Group (Lower Ordovician) of Ontario, Canada. Recent work by Yochelson and Copeland (1974) indicates that the beds containing this species are latest Canadian (late Early Ordovician) in age in Ontario. Two specimens from the Tanyard Formation of Texas (lower Lower Ordovician) are herein also assigned to R. calcifera (USNM 127908, 127909); these specimens were previously figured by Cloud and Barnes (1948).…”
Section: Ribeiria Bussacensis Tromelin 1877mentioning
confidence: 97%
“…R. calcifera is known from several localities in the Beekmantown Group (Lower Ordovician) of Ontario, Canada. Recent work by Yochelson and Copeland (1974) indicates that the beds containing this species are latest Canadian (late Early Ordovician) in age in Ontario. Two specimens from the Tanyard Formation of Texas (lower Lower Ordovician) are herein also assigned to R. calcifera (USNM 127908, 127909); these specimens were previously figured by Cloud and Barnes (1948).…”
Section: Ribeiria Bussacensis Tromelin 1877mentioning
confidence: 97%
“…This species was re-described by Yochelson & Copeland (1974, p. 205), and they noted, "...no close correspondence between the syntypes and the line drawings." Yochelson & Copeland (1974) noted the similarity of C. unguis and C. canadensis and suggested that they might be placed in synonymy, although they did not. No operculum has been associated with C. canadensis.…”
Section: Shell Of Ceratopea Cf C Unguis Yochelson and Bridge 1957mentioning
confidence: 99%
“…Several species of Ceratopea occur in western Newfoundland (Rohr et al 2000. Ceratopea normani (Billings, 1865), which is a synonym of C. canadensis Yochelson & Copeland (1974), is known from an internal mold from Billing's (1865) Unit G (Catoche Formation). Shells probably of C. canadensis occur in the Catoche Formation (Rohr et al 2000.…”
Section: Shell Of Ceratopea Cf C Unguis Yochelson and Bridge 1957mentioning
confidence: 99%
See 1 more Smart Citation
“…'Fhis is probably the lower siindg: division of the Oxfc~rd Formatic~n according to its recent revision by Bond and Greggs (1976, p. 22 Wilson (1946, p. 17) conclalded that the Oxford Formation is 'early Reekmantown' in age, but more recent age assignn-nents of the gastropod, cephalopod, and conodont suggest a somewhat younger age. Based on the presence of C,'cratopuks ccancrcJensis and other gastropods in the Oxford Formation of 0xfc)rd and Marlborough Townships, Yochelson and Copeland (1974) suggested a late Canadian to latest Canadian age for this form:ition. A similar age was indicated for the cephalopcads (Flower, in Uochelson and Copeland 1974).…”
mentioning
confidence: 99%